Variation in the fibroblast growth factor 23 (FGF23) gene associates with serum FGF23 and bone strength in infants - Enlund-Cerullo, Maria; Holmlund-Suila, Elisa; Valkama, Saara; Hauta-alus, Helena; Rosendahl, Jenni; Andersson, Sture; Pekkinen, Minna; Mäkitie, Outi (Frontiers in Genetics, 2023)
Introduction: The effects of genetic variation in fibroblast growth factor 23 (FGF23) are unclear. This study explores the associations of single-nucleotide polymorphisms (SNPs) of FGF23 with phosphate and vitamin D metabolism and bone strength in early childhood. Methods: The study is part of the vitamin D intervention in infant (VIDI) trial (2013–2016), in which healthy term infants born to mothers of Northern European origin received vitamin D3 supplementation of 10 or 30 μg/day from 2 weeks to 24 months of age (ClinicalTrials.gov NCT01723852). Intact and C-terminal FGF23 (cFGF23), 25-hydroxyvitamin D (25-OHD), parathyroid hormone, phosphate, and peripheral quantitative computed tomography (pQCT)-derived bone strength parameters were analyzed at 12 and 24 months. The study included 622 VIDI participants with genotyping data on FGF23 SNPs rs7955866, rs11063112, and rs13312770. Results: Rs7955866 minor allele homozygotes had lowest cFGF23 at both time-points (mixed model for repeated measurements, pvariant = 0.009). Minor alleles of rs11063112 were associated with a greater age-related decrease in phosphate concentration (pinteraction = 0.038) from 12 to 24 months. Heterozygotes of rs13312770 had the greatest total bone mineral content (total BMC), cross-sectional area (total CSA), and polar moment of inertia (PMI) at 24 months (ANOVA p = 0.005, 0.037, and 0.036, respectively). Rs13312770 minor alleles were associated with a greater increase of total BMC, but a smaller increase of total CSA and PMI, during follow-up (pinteraction <0.001, 0.043, and 0.012, respectively). Genotype of FGF23 did not modify 25-OHD. Conclusion: The study finds that genetic variation in FGF23 modifies cFGF23, phosphate, and pQCT-derived bone strength parameters from 12 to 24 months of age. These findings potentially promote an understanding of the regulation of FGF23 and its role in bone metabolism and temporal changes thereof during early childhood.